Pemanfaatan Model-model dalam Pelayanan Konseling untuk Membentuk Generasi Berkarakter Bebas Narkoba - Fadilla Yusri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
One of the unsettling society not only in Indonesia but also in the rest of the world is the circulation of drugs, especially among students. Not only consume, nowadays there are also students and the young generation which helped distribution, ranging from airport to the courier. Drug abuse is a social problem that always comes up in the midst of the community. Drug circulation increasingly bolder worrying; drugs became one of the nation's character Assassin. Indonesia was in a crisis of character. The spread of drug prevention efforts among the younger generation is supposed to be a shared responsibility, in this case all parties including parents, teachers, and the public should be aware of are active in contributing to the threat of drugs towards the younger generation. One way is to establish and improve the character of the young generation is by providing help through counseling. Counseling counselor should be done through a clear procedure, so that the process happens more effectively and right on target. Counselling is not solely the verbal sentence formulation, but also load the roles that run by counsellors and clients, the procedure is, and the behavior of clients that will be transformed in the process. Because of that in providing services to the client whether or not there are nine Sha-counseling model that can be used by counselors.